White Terror - Schweizer, Daniel (Dschoint Ventscher, 2005)
Versions: 90 min and 52 min. Verzio FF. Duration: 00:52:00 Over the past five years, new ideologists of radical far-right extremism have emerged all over Europe, North America and Russia. They do not necessarily shave their heads; they have created corporations, distribution companies, music clubs, magazines, publishing houses, internet sites and they have replaced the old symbols with new ones. With globalization taking a firmer hold and with clear demarcation lines blurring, the hate-mongers are rekindling the fires of the past, blowing on their glowing ashes. In this era of new technologies, the United States and Sweden have been deeply shocked to find their youth roused to racist violence, which has since contaminated the whole of the Western world as well as Russia and its neighbouring countries. For young Neo-nazis the past is virtual history where real cannot be distinguished from fake; their version of the future looks bleak and threatening. Daniel Schweizer investigates the forces that hide behind the «White Power» and the «New Racists» slogans.